New modified version of the Risk Adjustment for Congenital Heart Surgery category and mortality in premature infants with critical congenital heart disease - Young Mi Yoon; Seong Phil Bae; Yoon-Joo Kim; Jae Gun Kwak; Woong-Han Kim; Mi Kyoung Song; Seung Han Shin; Ee-Kyung Kim; Han-Suk Kim (The Korean Pediatric Society, 2020)
Background Despite advances in neonatal intensive care and surgical procedures, perinatal mortality rates for premature infants with congenital heart disease (CHD) remain relatively high. Purpose We aimed to describe the outcomes of premature infants with critical CHD and identify the risk factors including the new modified version of the Risk Adjustment for Congenital Heart Surgery (M-RACHS) category associated with in-hospital mortality in a Korean tertiary center. Methods This was a retrospective cohort study of premature infants with critical CHD admitted to the neonatal intensive care unit from January 2005 to December 2016. Results A total of 78 premature infants were enrolled. The median gestational age (GA) at birth was 34.9 weeks (range, 26.7-36.9 weeks), and the median birth weight was 1.91 kg (range, 0.53-4.38 kg). Surgical or percutaneous intervention was performed in 68 patients with a median GA at birth of 34.7 weeks (range, 26.7-36.8 weeks) and a median birth weight of 1.92 kg (range, 0.53-4.38 kg). The in-hospital survival rate was 76.9% among all enrolled preterm infants and 86.8% among patients who received an intervention. Very low birth weight (VLBW), persistent pulmonary hypertension of the newborn (PPHN), bronchopulmonary dysplasia (BPD), and M-RACHS category 5 or higher (more complex CHD) were independently associated with in-hospital mortality. For the 68 premature infants undergoing cardiac interventions, independent risk factors for mortality were VLBW, BPD, and CHD complexity. Late preterm infant and age at intervention were not associated with patient survival. Conclusion For premature infants with critical CHD, VLBW, PPHN, BPD, and M-RACHS category ≥5 were risk factors for mortality. A careful approach to surgical intervention and prenatal care should be taken according to CHD type and neonatal condition.